Penilaian Risiko TI Pada Website DosenIT Dengan Framework ISO 31000 Dan ISO 27002 - Gioferi, Gilfen; Yulhendri, Yulhendri (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
DosenIT is a website that contains information on computer science. the website is managed by various professionals in the IT field, from lecturers, IT staff, to students currently studying at the computer science faculty. The main focus on the DosenIT website consists of seven main discussions, namely troubleshooting, basic computer science, computer networks, IT lectures, software, hardware, and the latest technological developments. During the use of the DosenIT website, some disturbances or problems affected the website such as article spam, viruses, loss of article data, website could not be accessed and pages changed. So that it disrupts the running of the website and even paralyzes all business processes on the DosenIT website. The purpose of this study is to carry out a risk assessment - risks that can disrupt business processes on the DosenIT website. Collecting data in this study using the method of observation, interviews, and literature studies. The data analysis process uses the ISO 31000:2018 framework which consists of communication and consultancy, determining context, risk assessment, and risk treatment according to ISO 27002:2013. The results of research conducted on the DosenIT website found 2 low risk levels, 10 medium risk levels, and 2 high level risks.